2022
DOI: 10.1155/2022/2724635
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Research on the Sustainability of Traditional Music and the Adaptability of Ecological Environment

Abstract: Under the new situation, the world is showing a trend of becoming more and more open, and the frequency of cultural exchanges in China is also accelerating. In this case, traditional music has been impacted to a certain extent, which also affects the sustainable use of traditional music. This is the general law of cultural development, and the impact is also accompanied by vitality. The analysis of the sustainability of traditional music and the adaptability of the ecological environment, how to accurately imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…This technique uses the EFE and IFE matrices to analyze external factors (opportunities and threats) and internal elements (strengths and weaknesses) to define the development strategy. Analysis of external elements, such as opportunities and threats, is done using the External Factor Evaluation (EFE) matrix.To examine concerns pertaining to economic, cultural, social, environmental, demographic, legal, governmental, technological, and market rivalry challenges, external factor data is sought.A matrix called the Internal Factor Evaluation (IFE) is used to examine factors that are owned as strengths and weaknesses.To examine issues about multiple functional firms, such as from the management, finance, human resources, marketing, information systems, and production perspectives, internal factor data is required, [45].…”
Section: Discussionmentioning
confidence: 99%
“…This technique uses the EFE and IFE matrices to analyze external factors (opportunities and threats) and internal elements (strengths and weaknesses) to define the development strategy. Analysis of external elements, such as opportunities and threats, is done using the External Factor Evaluation (EFE) matrix.To examine concerns pertaining to economic, cultural, social, environmental, demographic, legal, governmental, technological, and market rivalry challenges, external factor data is sought.A matrix called the Internal Factor Evaluation (IFE) is used to examine factors that are owned as strengths and weaknesses.To examine issues about multiple functional firms, such as from the management, finance, human resources, marketing, information systems, and production perspectives, internal factor data is required, [45].…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%